Geographical distribution of dental operators in South Africa over the period 1972 - 1992 - van Wyk, P. J.; Kroon, J.; Cleaton-Jones, P. E. (My University, 1994)
Using data available on dentists for 1972, 1982 and 1992 and on dental therapists for 1992 the geographical distribution of dental operators (dentists/dental therapists) in South Africa was determined and the dental operator to population ratios were calculated. Over a period of 20 years the number of dentists in South Africa has increased by 135,6 per cent while the total population of the area has increased by 59,8 per cent. The lowest operator to population ratio was 1:4517 found in the PWV region, and the highest ratio was 1:48730, recorded in the Northern Transvaal. The greatest decrease in dental operator to population ratios occurred in Natal and Transvaal. The study shows that there is an imbalance in the geographic distribution of dental operators favouring large urban areas.
PK
Keywords: Dentists/supply & distribution; Professional Practice Location*/statistics & numerical data